A Fourier Method for Sidelobe Reduction in Equally Spaced Linear Arrays. Issue 4 (21st April 2018) - Safaai‐Jazi, Ahmad; Stutzman, Warren L.
Abstract: Uniformly excited, equally spaced linear arrays have a sidelobe level larger than −13.3 dB, which is too high for many applications. This limitation can be remedied by nonuniform excitation of array elements. We present an efficient method for sidelobe reduction in equally spaced linear arrays with low penalty on the directivity. The method involves the following steps: construction of a periodic function containing only the sidelobes of the uniformly excited array, calculation of the Fourier series of this periodic function, subtracting the series from the array factor of the original uniformly excited array after it is truncated, and finally mitigating the truncation effects which yields significant increase in sidelobe level reduction. A sidelobe reduction factor is incorporated into element currents that makes much larger sidelobe reductions possible and also allows varying the sidelobe level incrementally. It is shown that such newly formed arrays can provide sidelobe levels that are at least 22.7 dB below those of the uniformly excited arrays with the same size and number of elements. Analytical expressions for element currents are presented. Radiation characteristics of the sidelobe‐reduced arrays introduced here are examined, and numerical results for directivity, sidelobe level, and half‐power beam width are presented for example cases. Performance improvements over popular conventional array synthesis methods, such as Chebyshev and linear current tapered arrays, are obtained with the new method. Key Points: This paper presents a novel sidelobe reduction method for linear arrays that is fully analytical, allowing for rapid calculation of their radiation properties The penalty on the array directivity is smaller than or nearly equal to those of other sidelobe‐reduced arrays such as Chebyshev array Analytical expressions for element currents are presented, and numerical results for radiation properties of arrays with 3 to 100 elements are provided